High-efficiency PPy@MoS2 Core-Shell Heterostructure Photocatalysts for enhanced pollutant degradation activity - Yizhou Yang; Longlong Wei; Shengdi Luo; Xudong Yang (Results in Chemistry)
To combat the global energy crisis and reduce environmental pollution, nano-semiconductor photocatalysts have become widely used. In this paper, a novel core-shell heterostructure containing polypyrrole@molybdenum disulfide (PPy@MoS2) composites was synthesized using simple oxidative polymerization and hydrothermal methods. The photocatalyst is made of pyrrole as raw material, polyvinyl alcohol as protective agent, and Fe as catalyst. Polypyrrole nanoparticles are synthesized by oxidative polymerization. Then, sodium molybdate as molybdenum source, thiourea as sulfur source, hydroxylamine hydrochloride as reducing agent, and F127 as surfactant are added as template to synthesize PPy@MoS2 with a core-shell structure and an average size of 80 nm through hydrothermal method. The PPy@MoS2 core-shell heterostructure performs much better than pure PPy or MoS2 in full visible spectrum. Moreover, the PPy@MoS2 structure exhibits high photoactivity in degrading methylene blue (MB), reaching a decomposition efficiency of 99.3 %. And after being recycled and reused 5 times, its catalytic effect is still not less than 99.3 %. Besides, the prepared PPy@MoS2 nanocomposite possesses a high specific surface area and a remarkable heterostructure interface, which easily separates holes and electrons to improve the photodegradation ability. Thus, our proposed heterostructure nanomaterial has the potential to be utilized in a multitude of applications pertaining to the protection of the natural environment, including the treatment of water and the degradation of dyes that may contaminate water sources.